Cold-Water Corals and Ecosystems 2005
DOI: 10.1007/3-540-27673-4_60
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and management implications of deep-sea coral and fishing effort distributions in the Northeast Pacific Ocean

Abstract: Abstract. The conservation of deep-sea corals is of growing interest in the UnitedStates. A range of issues including biodiversity protection, conservation of seafloor habitats, and the role of deep-sea corals as essential fish habitat places greater significance on understanding the distributions of these corals and fishing activities. At the same time overfishing of some groundfish populations highlights the need for ecosystem-based management. Here we present records of habitat-forming deepsea corals from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…This knowledge has generated a widespread and alarming scientific consensus on the need for their protection and conservation (e.g. Roberts 2002;Morgan et al 2005;Brock et al 2009;Hourigan 2009;Buhl-Mortensen et al 2010). In this respect, the SML CWC province is a Fisheries Restricted Area (General Fisheries Commission for the Mediterranean -Regional Activity Centre for Specially Protected Areas, GFCM-RAC/ SPA, 2007) and CWC communities have been included in the lists of Vulnerable Marine Ecosystems (VME) (FAO 2009) and amongst proposed priority conservation areas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge has generated a widespread and alarming scientific consensus on the need for their protection and conservation (e.g. Roberts 2002;Morgan et al 2005;Brock et al 2009;Hourigan 2009;Buhl-Mortensen et al 2010). In this respect, the SML CWC province is a Fisheries Restricted Area (General Fisheries Commission for the Mediterranean -Regional Activity Centre for Specially Protected Areas, GFCM-RAC/ SPA, 2007) and CWC communities have been included in the lists of Vulnerable Marine Ecosystems (VME) (FAO 2009) and amongst proposed priority conservation areas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An added factor that creates a sense of urgency in protecting these unique organisms is their extreme vulnerability to disturbance. Several studies have shown that bottom fishing can damage or destroy cold-water corals, reducing the 3-dimensional complexity of the bottom topography and leading to decreased faunal biodiversity and biomass (Koslow et al 2001, HallSpencer et al 2002, Morgan et al 2005, Althaus et al 2009, Clark & Rowden 2009.…”
Section: Introductionmentioning
confidence: 99%
“…In our results, we suggest that, in the Alaskan region, suitable habitat for both Paragorgia and Primnoa was found throughout the Aleutian Islands and on many seamounts, and we agree with Heifetz (2002). For the BC-CA region, we proposed that suitable habitat for both families occurs along the shelf break and on seamounts, a suggestion also made in and Morgan et al (2005). On the generated habitat suitability maps, we only showed suitable and unsuitable habitat, defined most conservatively because of the coarse resolution of the data (see 'Methods', Bryan & Metaxas 2007).…”
mentioning
confidence: 74%